COMPARISON OF IPS LEARNING RESULTS USING MONOPOLY MEDIA AND POWER POINT MEDIA - Yuli Mulyawati; Resyi A Ghani (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
This research using comparative methods. The purpose of this research is to compare the learning outcomes of learning IPS by using Media Monopoly and Media Powerpoint . This research was conducted at SDN Katulampa 1 in Bogor City Class VA, and VB in August odd semester 2019/2020. The analysis technique used is the analysis prerequisite test which includes a normality test, a homogeneity test, then a research hypothesis is carried out using the t test. The results empirically n shows that there perbendingan learning outcomes in Media Monopoly seen in the average score - average N-Gain 8 5 de ngan mastery learning outcomes 92 %, while the average score - average N-Gain on Media Power Point that is equal to 75 with the thoroughness of the results belaja r 86 %. ) . And the results of testing the hypothesis states that H o rejected and H a accepted because t arithmetic (1.67469) t table (1.67469). Based on the above results, it can be concluded that there is a comparison of the results of learning by using Media Monopoly and Media Power Point , and Media efektif is Media Monopoly.